Evaluación de la gestión administrativa del centro de salud Tosagua tipo c - Macías Párraga, Beatriz Elizabeth (2019)
The purpose of the evaluation of the administrative management of the Tosagua Type C Health Center was to identify the processes in the administrative management and apply instruments for the evaluation of the quality of the service and thus to know the perspectives or opinions of the users - patients; for this, the interview was conducted with the director of the institution, which allowed to identify the processes that are generated within each area. Subsequently, the evaluation was carried out using the SERVQUAL model, achieving knowledge of the quality of service provision to the community, of the dimensions that make up said model; tangible elements, reliability, empathy, responsiveness and security. From this, these results were represented through statistical graphs for a better understanding, which helped to recognize the limited time of attention to the patient - user, scarce economic resources, among other problems detected by the instruments used in the research. Finally, on the basis of the problems detected, strategies were designed to improve them, the same ones that have objectives, activities, resources and people in charge in their structuring, among others; all with the purpose of providing a better service to the population in general.